2012
DOI: 10.1111/j.1365-2702.2012.04279.x
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac disease – women's experiences in everyday life

Abstract: Nurses should help women to adopt facilitating thoughts in relation to the disease and, in so doing, help them to select appropriate coping strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 33 publications
4
21
1
3
Order By: Relevance
“…Since the pain associated with endometriosis is cyclical in nature, that is, the intensity of the pain can be anticipated based on their menstrual cycle, patients could schedule activities and plan in order to cope. Planning has also been used as a coping strategy in patients with coeliac disease (Jacobsson et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the pain associated with endometriosis is cyclical in nature, that is, the intensity of the pain can be anticipated based on their menstrual cycle, patients could schedule activities and plan in order to cope. Planning has also been used as a coping strategy in patients with coeliac disease (Jacobsson et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Coping is an important concept in the field of chronic illness as it allows health-care practitioners to gauge the impact of a disease on patients. For this reason, coping has been investigated in relation to a number of chronic illnesses such as HIV (Stowers Johansen and Kohli, 2012), diabetes (Collins et al, 2009), coeliac disease (Jacobsson et al, 2012) and rheumatoid arthritis (Ramjeet et al, 2008). Among women, coping research has extended to areas such as coping with infertility (Lee et al, 2010), ovarian cancer (Price et al, 2013) and polycystic ovary syndrome (PCOS) (Benson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…) and also described aspects of being a woman living with CD (Jacobsson et al . ). In this study, using follow‐up interviews with the same women, we investigate whether patient education using PBL can influence the daily lives of women with CD.…”
Section: Introductionmentioning
confidence: 97%
“…Several papers reported lower QoL in women with CD than in celiac men. 9,[11][12][13]18 Finally, Paarlahti et al 47 reported that a long duration of symptoms before diagnosis, psychiatric, neurologic or gastrointestinal comorbidities and persistent symptoms were predictors of a reduced QoL.…”
Section: Qolmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Unfortunately, interest in the health perception of celiac patients has been affected by the lack of CD-specific QoL instruments allowing measurement of specific aspects of the disorder. Most studies exploring the QoL in CD patients used generic multi-item and multi-dimensional instruments developed for chronic disorders.…”
Section: Qolmentioning
confidence: 99%